Analysis Of Perceptions Of Financial Literacy And Financial Inclusion Of Coastal Village Communities In West Brandan District, Langkat Regency - Alfira Israfia; Lailan Safina Hasibuan (Proceeding International Seminar of Islamic Studies, 2019)
This study aims to analyze perceptions and what factors affect financial literacy and financial inclusion of coastal village communities in Babalan District, Langkat Regency. Accessibility of Financial Institutions (Y) as a bound variable. Income, Education and Information (X) as free variables in this study. The sampling technique used the Non-probability sampling method and obtained a sample of 35 respondents. The type of data used is primary data sourced from the results of the distribution of questionnaires and skunder data sourced from the Financial Services Authority. This research uses a factor analysis method. The results showed that information factors have an effect and are significant on the accessibility of financial institutions in coastal villages, West Brandan District, Langkat Regency. Income and Education Factors do not have an influence on the Accessibility of Financial Institutions. The development of Financial Literacy and Inclusion in Indonesia continues to experience a significant increase per three years, it's just that more ways are still needed to increase public interest in Financial Literacy and Inclusion.